2015
DOI: 10.1177/0951484815607540
|View full text |Cite
|
Sign up to set email alerts
|

Clinical leadership through commissioning: Does it work in practice?

Abstract: In tune with much international practice, the English National Health Service has been striving to transform health care provision to make it more affordable in the face of rising demand. At the heart of a set of recent radical reforms has been the launch of 'clinical commissioning' using the vehicle of local groups of General Practitioners (GPs). This devolves a large portion of the total healthcare budget to these groups. National government policy statements make clear that the expectation is that the group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…They point to relatively limited ambitions in some CCGs, and report the role of senior managers in encouraging or constraining such ambition, and conclude that there is a lack of good evidence for widespread larger scale change initiated by CCGs. 28 Our evidence provides important context for these findings, and suggests some important underlying mechanisms which may underpin these findings, in particular the variation in operational and strategic decision-making arrangements in CCGs, and the variation in the scope of roles played by GPs.…”
Section: Discussionmentioning
confidence: 62%
“…They point to relatively limited ambitions in some CCGs, and report the role of senior managers in encouraging or constraining such ambition, and conclude that there is a lack of good evidence for widespread larger scale change initiated by CCGs. 28 Our evidence provides important context for these findings, and suggests some important underlying mechanisms which may underpin these findings, in particular the variation in operational and strategic decision-making arrangements in CCGs, and the variation in the scope of roles played by GPs.…”
Section: Discussionmentioning
confidence: 62%
“…This NPM emphasis was supported by a study of a range of NHS boards (Storey et al, 2010), which found NEDs brought legal or business skills to the role, with a positive association between PCT NEDs' influence and "effective use of resources" reflected by an independent measure of organisational performance. However, within CCGs the NED role appears less influential in a more recent study by this team, focused primarily on GP leadership in CCGs, which also included NEDs as respondents (Storey et al, 2015;Marshall et al, 2018). The GPs and Executives were felt to be far more influential on service redesign and communicating with patients and the public than other board members including NEDs.…”
Section: Influence Of New Public Managementmentioning
confidence: 98%
“…Academic teaching centers play a key role in health innovation because of their expertise, skills and active involvement in clinical research (Lega et al, 2017;Storey et al, 2015). Yet, as our interviewees underscored, a hierarchical governance and physician-centered culture limit their capacity to engage a diversified set of innovation stakeholders (Busch-Casler et al, 2020).…”
Section: Implications For Healthcare Managersmentioning
confidence: 99%